Avaliação da compactação de cromatina espermática e morfometria da cabeça de espermatozoides de touros zebuínos e taurinos durante estação quente e fria na microrregião de Uberaba, MG, Brasil - Gruppi, Luiz Jerônimo Ferreira (2019)
Evidences suggests impaired reproductive performance of bulls caused by caloric stress, and Bos taurus indicus bulls are considered more resistant to this type of stress. However, it is not known whether correct management of bulls can minimize this deleterious effect during warmer periods of the year. The objective of the present study was to compare the quality of sêmen’s strows of B. taurus and B. indicus produced in winter and summer in the microregion of Uberaba, MG, Brazil. Samples were evaluated for sperm concentration, motility, sperm morphology, sperm head morphometry, decondensation and heterogeneity of sperm chromatin and the location of sperm chromatin decondensation. Concentration, motility and morphology assessments were performed as recommended by the Brazilian College of Animal Reproduction. Morphometric and sperm chromatin evaluations were performed using computational image analysis techniques of semen hydrolyzed with hydrochloric acid and stained with toluidine blue. The morphometric analyzes showed that in B. taurus the cells have larger area in strows produced in summer than in winter. When compared the morphometry of the doses between B. indicus and B.taurus, regardless of the season, the taurines showed larger area in their cells, compared to the zebu bulls. Fourier transform harmonic 2, side symmetry, decondensation and chromatin heterogeneity were also higher in the B. taurus group. When comparing the head region with chromatin decondensation, the B. tourus group presented higher number of normal cells (without chromatin changes) during the summer and higher decondensation in the basal half (DMB) of the heads during the winter. DMB was also higher in the B. taurus group compared to B. indicus, regardless of the season. And when compared all doses produced in summer with winter without considering clattle, winter doses showed higher number of DMB. When comparing the morphology, the strows produced in winter, regardless of race, presented higher number of cells with normal morphology than in summer doses, which presented higher number of minor defects. B. indicus’s strows tended to be more concentrated during summer than in winter. When compared all doses, regardless of cattle, summer presented higher concentration than strows produced during winter. In general there were not many differences between the strows produced during winter and summer, regardless of the races. These few differences may be linked to the management of bulls in the place where the strows were produced. The shading of paddocks and frequent bathing of animals during hot days may have softened the interference of heat stress in these animals, uniforming the quality of doses during the year.